Fully Ir(iii) tetrazolate soft salts: the road to white-emitting ion pairs - Fiorini, V.; D'Ignazio, A.; Magee, K.; Ogden, Mark; Massi, M.; Stagni, S. (2016)
The first examples of anionic Ir(iii) bis-tetrazolate complexes and their combination with a cationic Ir(iii)tetrazole derivative forming "fully tetrazolate" Ir(iii) based soft salts as O2-sensitive white emitters are described herein.